2015
DOI: 10.4067/s0717-95022015000400037
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Parameters of Ascending Aorta, Descending Aorta and Pulmonary Trunk by Computed Tomographic Angiography with Impact of Age, Hypertension, Smoking and Diabetes

Abstract: SUMMARY:This study aims at establishing whether transverse diameter (TD) and cross sectional-area (CSA) of the ascending aorta (AA), descending aorta (DA) and pulmonary trunk (PT) measured by computerized tomographic angiography (CTA) altered by sex, age, hypertension, smoking and diabetes. CTA examinations of the TD and CSA of the AA, DA and PT of 100 patients aged 49.5±16.9 years (range 16-78 years) selected between January 2009 to May 2011 from those referred to Radiology Department, Jordan University Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 30 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…It has also been demonstrated that age can remodel arteries in the form of thickening or thinning of the vascular wall [19]. These changes were observed by Shatarat et al, where the diameters of the pulmonary trunk and ascending aorta were decreased or increased in different age groups [20]. Blood vessels modulate their structure under different factors, especially wall shear stress, which may cause an increase in the diameter of the blood vessel wall mass [21], and it has been demonstrated that the histologic structure of the aorta is influenced by its function; thus, the elastin/collagen ratio is higher in the ascending aorta than in the descending aorta [22].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…It has also been demonstrated that age can remodel arteries in the form of thickening or thinning of the vascular wall [19]. These changes were observed by Shatarat et al, where the diameters of the pulmonary trunk and ascending aorta were decreased or increased in different age groups [20]. Blood vessels modulate their structure under different factors, especially wall shear stress, which may cause an increase in the diameter of the blood vessel wall mass [21], and it has been demonstrated that the histologic structure of the aorta is influenced by its function; thus, the elastin/collagen ratio is higher in the ascending aorta than in the descending aorta [22].…”
Section: Discussionmentioning
confidence: 87%
“…Diabetes causes vasculopathy, leading to microvascular and macrovascular complications [24]. These complications may alter the structure of the blood vessels; for example, it has been reported that DM significantly increases the transverse diameter of the descending aorta and intraluminal diameter of the ascending aorta in diabetic women [20]. In addition, it has been demonstrated that diabetic patients have smaller aortic root diameters than non-diabetic patients [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation